Influence of peer-based rehabilitation interventions for improving mobility and participation among adults with mobility disabilities: a systematic review. Issue 13 (18th June 2020) - Beaudoin, Maude; Best, Krista L.; Routhier, François
Abstract: Purpose: The prevalence of mobility disability reaches up to 20.5% among older adults. Mobility is a key factor of participation, thus rehabilitation interventions often aim to improve mobility and participation. Peer-based approaches to intervention delivery have become increasingly common. This study aims to identify peer-based rehabilitation interventions and summarize their influence on mobility and participation among individuals with mobility disabilities. Method: A systematic review was conducted using CINALH, EMBASE, MEDLINE, and PsycINFO. Articles that evaluated peer-based rehabilitation interventions for individuals with a mobility disability and assessed mobility or participation, as defined in the International Classification of Functioning, Disability and Health framework, were included. Study quality was assessed using the Physical Therapy Evidence Database and the Quality Assessment Tool for Before-After Studies With No Control Group. Results: Thirteen peer-based studies were identified. Six peer-led studies evaluated participation and two evaluated mobility. Seven professional-led studies evaluated participation and six evaluated mobility. Randomized controlled trials had fair to high quality. The quality of pre–post studies ranged from poor to good. Conclusion: Peer-based interventions should not be overlooked as a potential intervention strategy, but further research is needed to establish their influence on mobility and participation. Implications for rehabilitation: Peers offer a unique model of intervention that could support clinicians in their effort to improve mobility and participation outcomes for individuals with disabilities. There are currently two main models of peer-based interventions in rehabilitation: professional-led (peers assist professionals to facilitate the intervention) and peer-led interventions (peers facilitate the intervention). Both professional-led and peer-led models of intervention could be helpful in facilitating participation and in increasing mobility.